Measurement and Calculation of the Absorbed Dose During Irradiation of the Grain by a Pulse Electron Beam with Energy up to 160 keV; Energy Fluxes and Radiation Effects (EFRE-2020 online) - Vorobjev (Vorobyov) M. S. Maksim Sergeevich; Doroshkevich S. Sergey; Pokrovskaya E. A. Elena Aleksandrovna; Artemov (Artyomov) K. P. Konstantin Petrovich (2020, 2020)
Title screen